Mengelola Kinerja Bisnis Yang Dipengaruhi Oleh Orientasi Pasar Dan Inovasi Bisnis - Kurniawan, Iwan; Taufik, Taufik (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The aim of this research is to determine and analyze the impact of market orientation and innovation on the business performance of small and medium-sized enterprises (SMEs). The object of this research was small and medium-sized enterprises (SMEs). Research based on descriptive quantitative methods, through survey methods using closed questionnaire instruments. The sampling technique was purposive non-probability sampling involving the participation of 35 respondents. The analysis used to measure the influence of the dependent variable on the independent variable includes: Validity Test, Reliability test, Data Normality test, Correlation test, Determination Coefficient, Regression test, T test and F test. The results of this research can be seen that market orientation and business innovation, both partially and simultaneously have a significant positive effect on business performance. The findings of this research can attract the attention of business people to continue to strive and improve market orientation and innovation in an effort to achieve and improve business performance. The obtained results strengthen a reliable basis for the development of market orientation and innovative business due to the created business performance.